2012
DOI: 10.1002/art.33488
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic characteristics of intrarenal T cells: Trafficking of expanded CD8+ T cell β‐chain clonotypes in progressive lupus nephritis

Abstract: Objective To better define the immunologic character of the T cell infiltrate in lupus nephritis. Methods We performed double immunohistochemical staining and clonotypic T cell receptor (TCR) beta-chain sequencing in multiple anatomic regions isolated by laser-capture microdissection from renal biopsies. Results SLE kidneys have a variably patterned and often extensive infiltrate of predominantly clonally expanded T cells of CD4 and CD8 lineages. CD4 T cells were prominent in nearly two-thirds of SLE biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 57 publications
5
82
0
Order By: Relevance
“…Unlike in other organs, including the skin, lung, and intestine, [19][20][21][22][23] CD8 + T cells are the main effector T cells defending against intracellular pathogens and tumors, and they have been found in interstitial and periglomerular regions in kidney disease. [41][42][43] A critical role for CD8 + T cells in GN is supported by the attenuation of autoimmune nephrotoxic nephritis in CD8-knockout mice or induction of glomerular injury by adoptive transfer of antigen-specific CD8 + T cells. 12,44,45 Our previous study demonstrated that CD8 + T cells display a pathogenic role in AN mice.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in other organs, including the skin, lung, and intestine, [19][20][21][22][23] CD8 + T cells are the main effector T cells defending against intracellular pathogens and tumors, and they have been found in interstitial and periglomerular regions in kidney disease. [41][42][43] A critical role for CD8 + T cells in GN is supported by the attenuation of autoimmune nephrotoxic nephritis in CD8-knockout mice or induction of glomerular injury by adoptive transfer of antigen-specific CD8 + T cells. 12,44,45 Our previous study demonstrated that CD8 + T cells display a pathogenic role in AN mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found a resident memory CD8 + T cell population, identified based on gene expression similarity to T-RM cells described in other tissues 24,25 , and present in LD and LN samples. Prior immunohistochemical analyses have revealed CD8 + T cells localized to different areas of the kidney 40 ; it will therefore be of interest to determine whether the observed CD8 + T cell populations, as well as NK cells, show distinct renal localization and functions in autoimmunity.…”
Section: Cc-by-nc-nd 40 International Licensementioning
confidence: 99%
“…+ T-cells are associated with lupus pathogenesis, since infiltrating CD8 + T-cells into a lupus kidney indicates that they have the potential to mediate kidney injury (Winchester et al, 2012). It has been reported that TIM-3 negatively regulates the activation of macrophages in the kidney during nephrotoxic serum nephritis, and TIM-3 blockade aggravates nephritis by increasing the number of kidney-infiltrating inflammatory cells, which provides the evidence that TIM-3 exerts protective roles in the course of nephritis (Schroll et al, 2010).…”
Section: Discussionmentioning
confidence: 99%